Consensus on virtual management of vestibular disorders: urgent versus expedited care - Shaikh,AG; Bronstein,A; Carmona,S; Cha,Y-H; Cho,C; Ghasia,FF; Gold,D; Green,KE; Helmchen,C; Ibitoye,RT; Kattah,J; Kim,J-S; et al. (The Cerebellum: an international journal from neurosciences to clinical perspectives, 2020)
The virtual practice has made major advances in the way that we care for patients in the modern era. The culture of virtual practice, consulting, and telemedicine, which had started several years ago, took an accelerated leap as humankind was challenged by the novel coronavirus pandemic (COVID19). The social distancing measures and lockdowns imposed in many countries left medical care providers with limited options in evaluating ambulatory patients, pushing the rapid transition to assessments via virtual platforms. In this novel arena of medical practice, which may form new norms beyond the current pandemic crisis, we found it critical to define guidelines on the recommended practice in neurotology, including remote methods in examining the vestibular and eye movement function. The proposed remote examination methods aim to reliably diagnose acute and subacute diseases of the inner-ear, brainstem, and the cerebellum. A key aim was to triage patients into those requiring urgent emergency room assessment versus non-urgent but expedited outpatient management. Physicians who had expertise in managing patients with vestibular disorders were invited to participate in the taskforce. The focus was on two topics: (1) an adequate eye movement and vestibular examination strategy using virtual platforms and (2) a decision pathway providing guidance about which patient should seek urgent medical care and which patient should have non-urgent but expedited outpatient management.